2022
DOI: 10.23887/jpbi.v10i1.44748
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of Learning Media: Quizizz Application in EFL Remote Learning

Abstract: During Pandemic of Covid-19, the teachers require to improve their skill in using the technology to conduct the remote teaching-learning process more conducive. Therefore, the teachers need to master using the technology besides their material. Quizizz is one kind of application that can support the teaching-learning process because it has many interesting features in it. The aims of this research are to analyse the effectiveness of Quizizz to implement during the remote teaching-learning process. The instrume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…Some studies have been carried out on the effect of using games on vocabulary learning. For example, some studies (Kalogiannakis & Papadakis, 2019;Ade Indrayana, 2022) have shown positive effects on vocabulary acquisition, and one of them showed a negative effect on learning. Four studies stated that the more exposure the learners have to games, the better the acquisition of vocabulary words is as long as such activities incorporate clear teaching and learning goals.…”
Section: Effects Of Games On Vocabulary Skillmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have been carried out on the effect of using games on vocabulary learning. For example, some studies (Kalogiannakis & Papadakis, 2019;Ade Indrayana, 2022) have shown positive effects on vocabulary acquisition, and one of them showed a negative effect on learning. Four studies stated that the more exposure the learners have to games, the better the acquisition of vocabulary words is as long as such activities incorporate clear teaching and learning goals.…”
Section: Effects Of Games On Vocabulary Skillmentioning
confidence: 99%
“…Three studies (Silsüpür, 2017;Kalogiannakis & Papadakis, 2019;Ade Indrayana, 2022) used games to promote interactions between the people engaged in the English class. One of the studies stimulated interactions between the teacher and the student.…”
Section: Effects On Students' Interactionmentioning
confidence: 99%
“…Some studies have been carried out on the effect of using games on vocabulary learning. For example, some studies (Kalogiannakis & Papadakis, 2019;Ade Indrayana, 2022) have shown positive effects on vocabulary acquisition, and one of them showed a negative effect on learning. Four studies stated that the more exposure the learners have to games, the better the acquisition of vocabulary words is as long as such activities incorporate clear teaching and learning goals.…”
Section: Effects Of Games On Vocabulary Skillmentioning
confidence: 99%
“…Three studies (Silsüpür, 2017;Kalogiannakis & Papadakis, 2019;Ade Indrayana, 2022) used games to promote interactions between the people engaged in the English class. One of the studies stimulated interactions between the teacher and the student.…”
Section: Effects On Students' Interactionmentioning
confidence: 99%